2012
DOI: 10.1016/j.jpeds.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Safe Infant Sleep Recommendations on the Internet: Let's Google It

Abstract: Objectives To determine the accuracy of information on infant sleep safety on the internet using Google. We hypothesized that the majority of websites would accurately reflect the AAP recommendations for infant sleep safety. Study design We searched for advice using 13 key phrases and analyzed the first 100 websites for each. Websites were categorized by type and assessed for accuracy of information provided, based on AAP recommendations. The accuracy of information was classified as “accurate,” “inaccurate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 23 publications
6
62
1
2
Order By: Relevance
“…according to previously published criteria, reproduced in part with examples from this study in online supplementary eTable 2,23 and adherence to 17 general web page technical criteria reflecting proper disclosures, sources of evidence and features that improve site usability such as an internal search engine. The technical criteria were derived from a previously published review of studies assessing the quality of health information for consumers on the internet27 and are listed in online supplementary eTable 3.…”
Section: Methodsmentioning
confidence: 99%
“…according to previously published criteria, reproduced in part with examples from this study in online supplementary eTable 2,23 and adherence to 17 general web page technical criteria reflecting proper disclosures, sources of evidence and features that improve site usability such as an internal search engine. The technical criteria were derived from a previously published review of studies assessing the quality of health information for consumers on the internet27 and are listed in online supplementary eTable 3.…”
Section: Methodsmentioning
confidence: 99%
“…5 Furthermore, a large amount of information regarding the topic that caregivers may find on the internet is inconsistent with the latest AAP guidelines. 6 The current study attempts to illuminate some of the attitudes and factors that may influence the decision to adopt infant sleep safety and SIDS risk reduction behaviors among the caregivers of newborns and infants. The more health care providers understand about sleep related death and all its related aspects, the better equipped they will be to offer meaningful modeling and direction to families.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the sheer amount of information available, infant sleep safety recommendations from media sources may also contradict recommendations from health care providers and health educators. Studies have found that the influence of magazine advertisements [21] and incorrect information found in Google searches [22] may contribute to the mixed messages parents receive and influence how they negotiate safe sleep recommendations. Parents would also negotiate safe sleep messages once they are knowledgeable about them.…”
Section: Introductionmentioning
confidence: 99%